Experience in waterfowl management under the conditions prevailing in the Latvian S.S.R - Mihelsons, H; Viksne, J; Lejins, G (Wildfowl, 1967)
Trials and observations in Latvia show that for the preservation of the resources of waterfowl and their nesting populations in densely populated localities a complex of the following preservation and biotechnical measures is needed: 1. Complete cessation of human economic activity and of the sojourn of humans during the spring and summer on areas of reservoirs suitable for nesting of birds, on grassy islands and peninsulas; 2. Adaptation of existing islands and peninsulas for intensive nesting of ducks; (a) by cutting trees and bushes growing on them; (b) by complete destruction of reeds on the inner part of islands; (c) by arranging wide passages to the open water in belts of dense growth around islands; 3. Construction of small artificial grassy islands; 4. Permanent maintenance of intensive nesting grounds, by control of overgrowing by trees, bushes and reeds, and by preventing the formation of compact reed banks and thickets of other plants in the accesses to the water; 5. Reduction to a minimum of the number of raptorial birds and beasts which destroy nests in the vicinity of large nesting grounds of waterfowl; 6. Establishment of zones in which hunting is banned, so as to offer shelter to the birds during the hunting season.